SINTESIS DAN UJI TOKSISITAS ANALOG FLAVANON TERSUBSTITUSI HALOGEN - Rush, Ibnu; Teruna, Hilwan Yuda; Zamri, Adel (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Flavanones have been reported to possess many of interesting biological  activities  such as antimicrobe, antitumor, antioxidance, antiinflammatory, antimalaria, anticancer, and anti-HIV. In this research, a  halogenated flavanone 2-(3 -bromophenyl)chroman-4-one was synthesized by cyclization of  (E)-3-(3-bromophenyl)-1-(2-hydroxyphenyl)-2-propen-1-one  using  sodium  acetate as catalyst  under microwave  irradiation. The compound showed a good yield, and then was characterized by UV, IR and 1 H-NMR spectroscopy. The toxicity activity of this  compound was determined using Brine Shrimp Lethality Test (BSLT) method against larvae Artemia salina  Leach and showed a good activity with LC50  = 0,457 µg/mL. The result indicated that this compound  was potential  as anticancer.